„Powinieneś umieć się uczyć” – staropolskie rady jak się uczyć, aby się nauczyć (ciąg dalszych rozważań o tym, że wszystko już było) - Żołądź-Strzelczyk, Dorota (Studia Edukacyjne, 2022)
In old Polish philosophical and pedagogical thought, comments on learning appear rarely. As a rule, the relevant recommendations are addressed to those who teach and show how and what to teach, how to educate, and how to deal with the learner. The perspective of the other side, i.e. the learner, is most often omitted in general treatises, but is found in texts addressed to specific individuals, such as parental instructions or letters. The article draws on the works of Szymon Marycjusz and Stanisław Sokołowski where such remarks appear as well as on parental instructions written down when sons have left their family homes and set off for schools or on educational journeys. Both the authors and the fathers drew attention to several issues related to the subject under discussion. These include recommendations on how to or-ganize work appropriately, cautions relating to wasting time, and tips on how best to schedule time. They also include remarks on how to learn by emphasizing the importance of memorizing, practicing memory, taking notes, reading and conversation.